Globalization and Another Conceptions – Search for New Approaches to International Relations (Czech Journal of International Relations, 1997)
A substantial transformation has begun in our way of perceiving the world. Expressed in terms used by Thomas Kuhn (Kuhn, 1962), what has often been presented as four centuries of "normal science" in politics and international affairs, i.e. "Westphalian" or realist an understanding that a priori postulates that quiet "players" in international relations are (later nation-states), is questioned by a sufficiently wide range of empirical ones research, in which theorists systematically try to find an alternative "paradigm". In recent years, globalization has become the main contender for this status.There are two problems with this supposed "paradigm shift". Chief among them is the fact that the old paradigm is still very much alive. After all, once institutions and social structures crystallize, they lock themselves into certain modes of behavior. As Talcott Parsons noted, the elements of social change must reach a cumulative threshold even before existing systems change. Thus, the state as an institutional structure "does not yield", but in fact it has new and more complex functions in our more open and interdependent world. The second problem is the fact that globalization itself is a "volatile" concept, which is highly questionable both in terms of its actual existence and its basic form.